Smartphone Application on Perioperative Cardiac Surgery: A Systematic Review - Sidik Awaludin; Elly Nurachmah; Dwi Novitasari (Universitas Aisyah Pringsewu, 2022)
Information technology used in the health sector is known as e-health. Smartphone applications are starting to be widely used for long-term condition monitoring management in the medical and health fields. Perioperative cardiac surgery procedures require long-term monitoring. This study aimed to find out about smartphone use in perioperative cardiac surgery. A systematic review design. The reporting framework uses Featured Reporting Items for Systematic Review and Followed Meta-analysis to report findings. Data Sources, CINAHL, ProQuest, Science Direct, and Google Scholar searched for English-language articles published from January 2010 to August 2020 with the keywords